Penetrance, pleiotropy, and psychiatry 2 - Vorstman, Jacob A.S. (Henry Stewart Talks, 2021)
Using 22q11.2 deletion to examine pleiotropy and variable penetrance, Common variants influence rare, high impact genetic variants expression, Clinical applications for patients with neurodevelopmental disorders